2021
DOI: 10.3390/md19060286
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Bioinformatic Analysis for Keratinase Detection in Marine-Derived Streptomyces

Abstract: Keratinases present promising biotechnological applications, due to their ability to degrade keratin. Streptomyces appears as one of the main sources of these enzymes, but complete genome sequences of keratinolytic bacteria are still limited. This article reports the complete genomes of three marine-derived streptomycetes that show different levels of feather keratin degradation, with high (strain G11C), low (strain CHD11), and no (strain Vc74B-19) keratinolytic activity. A multi-step bioinformatics approach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 107 publications
(164 reference statements)
1
10
0
Order By: Relevance
“…It is worth mentioning that strain CHD11 showed high feather degradation in tubes after 15 days of culture (qualitative tests, Figure 2), explaining the fact of the slight increase in the curves of keratinolytic activity and concentration of sulfhydryl groups up to 5 days of culture, evidencing a slower metabolism in this strain. These results were consistent with the in-silico analysis reported by Valencia et al [40], who reported some putative proteases phylogenetically close to known keratinases in the genome of Streptomyces sp. CHD11.…”
Section: Screening Of Keratinolytic Actinobacteria In Liquid Mediumsupporting
confidence: 93%
See 3 more Smart Citations
“…It is worth mentioning that strain CHD11 showed high feather degradation in tubes after 15 days of culture (qualitative tests, Figure 2), explaining the fact of the slight increase in the curves of keratinolytic activity and concentration of sulfhydryl groups up to 5 days of culture, evidencing a slower metabolism in this strain. These results were consistent with the in-silico analysis reported by Valencia et al [40], who reported some putative proteases phylogenetically close to known keratinases in the genome of Streptomyces sp. CHD11.…”
Section: Screening Of Keratinolytic Actinobacteria In Liquid Mediumsupporting
confidence: 93%
“…A recent bioinformatics analysis, based on a genomic comparison of Streptomyces sp. G11C, with two Streptomyces strains with differential keratinolytic activity, allowed the identification of a set of putative proteases that could potentially be involved in its keratinolytic capacity: seven putative keratinases and 17 putative proteases, unique to strain G11C [40]. In this study, we identified 18 of these proteases in the secretome, including six of the predicted putative keratinases (Table 2).…”
Section: Secretome Analysis Of Streptomyces Sp G11cmentioning
confidence: 80%
See 2 more Smart Citations
“…The phylogenetic tree based on these 120 ubiquitous genes was reconstructed by IQ-TREE [ 37 ] using the LG+F+I+G4 model and 1000 bootstrap replicates. Some other analysis methods referred to the previous published articles [ 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%